Diagnosis, Management, and Outcome of Bart's Syndrome Observed in a Sub-Saharan African Country (Senegal, Dakar): 2 Case Reports - Mame Téné Ndiaye Diop; Maimouna Bassoum; Khadim Diop; Yaye Diood Dieng; Birame Seck; Fatou Diasse Fall; Charles Tchibinda Delicat; Alassane Ndiaye; Assane Diop; Maodo Ndiaye; Pape Moctar Faye; Moussa Diallo; et al. (Karger Publishers, 2023)
Introduction: Bart's syndrome is an uncommon inherited congenital disorder associating congenital cutaneous aplasia of the extremities and inherited epidermolysis bullosa. Bilateral and symmetrical involvement of the limbs is exceptionally described on black skin. In most cases, the diagnosis is clinical; however, the management remains very difficult and the extended forms are a real therapeutic challenge. We report 2 cases of Bart's syndrome observed in a sub-Saharan African country (Senegal, Dakar). Case Presentation: It was about 2 premature female and male newborns. On physical examination, the girl presented with a total absence of skin on the limbs, associated with cutaneous detachment of the trunk representing a detached and detachable skin surface of 46%; the boy underwent a total absence of skin of more than 50% of the skin surface. The diagnosis of Bart's syndrome was set based on the typical clinical aspect. The blood count and CRP were normal for the girl whereas it revealed some disorders for the boy. The 2 newborns were urgently admitted to an incubator, and the intensive care was started with hyperhydration, anti-staphylococcal prophylaxis, and daily dermatological care with antiseptic baths and fatty dressings. Conclusion: Bart's syndrome is an uncommon genodermatosis characterized by a clinical triad associating congenital cutaneous aplasia of the extremities, inherited epidermolysis bullosa suspected in the presence of bubbles, and areas of cutaneous fragility and nail deformity. All types of which can be associated with this syndrome. The easy clinical diagnosis but the difficult management encumber the vital prognosis of our cases.